2021
DOI: 10.1007/s00466-021-02098-y
|View full text |Cite
|
Sign up to set email alerts
|

Fast and multiscale formation of isogeometric matrices of microstructured geometric models

Abstract: The matrix formation associated to high-order discretizations is known to be numerically demanding. Based on the existing procedure of interpolation and lookup, we design a multiscale assembly procedure to reduce the exorbitant assembly time in the context of isogeometric linear elasticity of complex microstructured geometries modeled via spline compositions. The developed isogeometric approach involves a polynomial approximation occurring at the macro-scale and the use of lookup tables with pre-computed integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
(149 reference statements)
0
12
0
Order By: Relevance
“…In this sense, our method is consistent with the current development of open-source IG libraries (see, e.g., Nutils (http://www.nutils.org) or pyiga (https://github.com/c-f-h/pyiga) as Python libraries, tIGAr [40] for a FENICS-based implementation, and YETI (https://lamcosplm.insa-lyon.fr/projects/yeti/) for a Fortran-Python implementation). Even more interestingly, since the IG code is only used at the global scale, where standard elasticity may be sufficient, our strategy also appears totally relevant with the newly developed fast assembly and solution procedures for IGA in the linear regime (see, e.g., sum factorization [58], use of look-up tables [59,60], weighted quadrature [61], and domain decomposition solvers [62,63]).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our method is consistent with the current development of open-source IG libraries (see, e.g., Nutils (http://www.nutils.org) or pyiga (https://github.com/c-f-h/pyiga) as Python libraries, tIGAr [40] for a FENICS-based implementation, and YETI (https://lamcosplm.insa-lyon.fr/projects/yeti/) for a Fortran-Python implementation). Even more interestingly, since the IG code is only used at the global scale, where standard elasticity may be sufficient, our strategy also appears totally relevant with the newly developed fast assembly and solution procedures for IGA in the linear regime (see, e.g., sum factorization [58], use of look-up tables [59,60], weighted quadrature [61], and domain decomposition solvers [62,63]).…”
Section: Discussionmentioning
confidence: 99%
“…This is done via functional composition, meaning that the subdomains are the images of the composed mappings: normalΩfalse(sfalse)=false(Gfalse(sfalse).2em.2emTfalse)false[truenormalΩ˜false].$$ {\Omega}^{(s)}=\left({G}^{(s)}\circ T\right)\left[\tilde{\Omega}\right]. $$ More information regarding this multiscale geometric representation can be found in References 31,46 for instance.…”
Section: Application To Multiscale Geometric Modelsmentioning
confidence: 99%
“…They are generic in terms of applications but they may not appear optimal in the specific context of lattice structures. In particular, they do not make use of the geometric similarity among different cells in the numerical solution, what allows a drastic reduction in terms of memory and computational cost, as demonstrated for the assembly of the numerical operators in Reference 31. The objective of this work is to bring forward this idea of benefiting from the repetitive character of the lattice geometries to build a dedicated HPC solver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various structural topology optimization methods have been adopted by researchers to improve the material distribution of engineering structures [20][21][22][23]. While some researchers have used internal microstructure-based material optimization methods and proposed various microstructures to improve material efficiency [24][25][26][27][28]. However, to the author's best knowledge, there is no study found in the literature that has focused on implementing any such methodology for the optimization of any shredding system.…”
Section: Introductionmentioning
confidence: 99%